EFEKTIVITAS MINUMAN BERENERGI DARI BUAH PISANG DAN GULA KELAPA TERHADAP INDEKS KELELAHAN OTOT - DEWA FAJAR JUNE PRABOWO, PUTRA; NOORDIA, ANNA (Jurnal Kesehatan Olahraga, 2019)
Abstract EFFECTIVENESS OF ENERGY DRINK FROM BANANAS AND COCONUT SUGAR ON THE INDEX OF MUSCLE FATIGUE Athletes who exercise with an aerobic-anaerobic combination often experience muscle fatigue. Muscle fatigue is a condition when muscles lose the ability to contract after strong or long muscle contractions. Efforts to overcome fatigue when exercising with the type of anaerobic endurance requires an intake that serves as a support for the athletes anaerobic endurance level in the sport. The purpose of this study was to identify the effectiveness of energy drinks from bananas and coconut sugar to index of fatigue. This research is an experimental study with a one group pre-test post-test design, namely the design that has a pre-test before being given treatment and post-test after being treated and comparing the results of the pre-test and post-test. The research sample was 8 people. Because the value of F table is 8.8> 4.6. Then F count> F Table (8.8> 4.6), then H0 is rejected. The results of the study obtained the results of the average index of fatigue in the pre test is 6,653. While the average value of the post test is 4,154. From the two tests, the provision of energy drinks from bananas and coconut sugar (post test) can reduce index value of muscle fatigue. So it can be concluded that the administration of energy drinks from bananas and coconut sugar has been shown to be effective against the index of muscle fatigue. Keywords : RAST Test, Energy Drink, Index of Muscle Fatigue